The Effectiveness of Fiqh Rules on Law Number 16 of 2019 - Hertasmaldi, Hertasmaldi; Sulfinadia, Hamda; Mardianto, Mardianto; Abdul Razak, Dudung; Efendi, Faisal (Samara: Journal of Islamic Law and Family Studies, 2025)
Legal certainty must be present in a law or regulation. Without legal certainty, the rights of legal subjects will be violated and neglected. Similarly, without legal certainty, legal subjects will feel anxious and insecure because they feel that the law does not protect them. Law Number 16 of 2019 concerning Amendments to Law Law No. 1 of 1974 is considered to lack legal certainty and clarity, as the determination of the marriage age limit in that law is based solely on Law No. 35 of 2014 on Amendments to Law No. 23 of 2002 on Child Protection. This type of research is library research. Library research is a series of activities related to the methods of collecting library data, reading and recording, and processing research materials. Law No. 16 of 2019 still allows Indonesian society to engage in child marriage under the legal age. This law must be considered from various legal perspectives and have clear legal consequences, so a comprehensive revision of this law is necessary. Even if possible, Law No. 1 of 1974 should be reviewed and adjusted to the legal issues that exist now and in the future. By applying the concept of public interest and rejecting harm in a law or regulation, the objectives of that law or regulation will be achieved and become effective.